(untitled) (Olhar de Professor, 2023)
This article is the result of the monograph carried out in the degree course in Music at the Federal University of Roraima and aimed to present musical pedagogical activities based on regional songs presented at the Roraima Music Festivals, based on the guidelines of the National Curricular Common Basis (BNCC) and the Composition, Audition, Performance, Literature and Skills acquisition (C(L)A(S)P) by Swanwick, the songs were taken from the CD Finalistas do Festival Canto Forte. To the construction of theoretical references on the subject, it became important to discuss music festivals in Roraima, about regional identity through the artistic manifestations of the Canto Forte Music Festival, of the C(L)A(S)P model and current legislation. The result of this research is the elaboration of twelve lesson plans for basic education with regional songs and BNCC guidelines apply. The research arose in the sense of seeking other ways to teach music in Roraima, in addition to nationally known songs, and the unfolding of this research allowed the elaboration of lesson plans for basic education based on regional songs applicable to the guidelines of the BNCC.